Interpreting the Sustainable Development Goals through the Perspectives of Utopia and Governance. Issue 2 (4th May 2021) - Eskelinen, Teppo
Abstract: The article analyses the Sustainable Development Goals (SDGs) from the perspective of their self-understanding of political sense expressed in key SDG documents, including both UN documents and reports produced by individual countries. Utopia and governance are presented as ideal-typical approaches and analytical tools for qualitative content analysis. This approach is argued to be particularly illuminating in the case of politics of international development, as international development is simultaneously highly utopian and deeply embedded in rationalities of governance. As this analytical framework is applied to the SDGs, it is shown that their utopian pronouncements are related to the idea of humanity as a single subject, as well as inclusive prosperity. On the other hand, the SDGs are curtailed by adherence to the ideas of contemporary governance, the international order and given ideas of development economics. The findings and the methodology are then further discussed in the broader context of international development.